Authentic Listening to Student Voice: The Transformative Potential to Empower Students with Social, Emotional and Behavioural Difficulties in Mainstream Education - FLYNN, PAULA (University of Dublin, Trinity College Dublin, 2013)
This student voice study engages with the perspectives of twenty student participants in mainstream education on their experience of school. All of the participants were identified as at risk of educational exclusion or with internalising or externalising behaviours associated with the classification of `social, emotional and behavioural difficulties? (SEBD). It was integral to this research undertaking to determine if `being listened to? would empower the participants to transform their experience of school. The methodology is an example of qualitative research using a combination of ethnographic and narrative approaches. Data was collected primarily through one to one interviews and focus group meetings with the student participants, and supported by insights recorded in a reflective journal and contributions from school personnel. The data is presented within case studies and analysed thematically with collaborative contributions of significant themes from the participants. The major themes that emerged from the data were: `Voice?, `Perspectives of Difference?, `Care? and `Leadership?. The findings of this research demonstrated that having the opportunity to be heard was significant to all of the participants. However, for some of the young people who were `silenced? on important issues in other parts of their lives, the experience of this `voice? process had less impact. For many of the participants, the opportunity to talk and encounter an `authentic response? influenced their levels of enthusiasm for and participation in the research process. This study confirmed the potential relationship between `voice?, `empowerment? and `transformation? because most of the participants actively contributed to improving relationships with their teachers and peers, while promoting and participating in strategies and activities that impacted positively on their experience of school. Students with labels that exemplify `difficult difference? were responsible for positively affecting changes in attitudes towards them and presenting a model for the development of relationality in care and leadership. This evidence suggests that a `student voice? approach to supporting young people is fundamental to the development of an inclusive learning environment for the benefit of all students.
PUBLISHED
Keywords: Student Voice; Social, Emotional and Behavioural Difficulties; Identities in Transformation; Inclusive Society